MAKAM MAHALIGAI DAN PAPAN TINGI DALAM PEMBELAJARAN IPS - Kusnadi Kusnadi; Nurul Hidayah Azima; Mia May Sarah; Selfia Diva Ariwana; Ainaya Azzahro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The marginalization of Barus' ancient maritime identity from the collective memory of national history and the passive packaging of contextual teaching media are the background to this research activity. This problem triggers a bias in students' understanding in reconstructing the chronological route of the Indonesian spice trade route. The main focus of this scientific study is to analyze the historical value and socio-religious existence of the Mahligai and Papan Tinggi Tomb sites to be formulated as supporting materials for Social Studies learning. The steps of this qualitative field research with a descriptive analytical design were operated through purposive sampling of informants involving regional tourism agencies, traditional leaders, and local religious figures. The primary data collection procedure was collected through direct observation techniques, in-depth interviews, and epigraphic studies of the remains of ancient Arab-Persian tomb inscriptions. The research findings indicate that the tomb complex contains more than 215 tombstones, including a two-meter-high tomb marker for Sheikh Mahmud, who died in 44 Hijri. The presence of these artifacts confirms Barus' role as a multi-ethnic international port and a gateway for Islamization in the 7th century AD. The main conclusion confirms that integrating local archaeological heritage into the curriculum has proven effective in sustainably enhancing students' spatial agility. Social studies teachers are recommended to design teaching modules based on the consistent use of archaeological heritage. ABSTRAK Terpinggirkannya identitas maritim kuno Barus dari ingatan kolektif sejarah nasional serta kepasifan pengemasan media ajar yang kontekstual melatarbelakangi kegiatan penelitian ini. Masalah tersebut memicu adanya bias pemahaman para siswa dalam merekonstruksi rute kronologis jalur perdagangan rempah nusantara. Fokus utama kajian ilmiah ini adalah menganalisis nilai historis serta eksistensi sosioreligius situs Makam Mahligai dan Papan Tinggi guna diformulasikan sebagai materi pendukung pembelajaran Ilmu Pengetahuan Sosial. Langkah-langkah penelitian kualitatif lapangan dengan desain deskriptif analitis ini dioperasikan melalui penarikan informan secara purposive sampling yang melibatkan instansi pariwisata daerah, pemuka adat, dan tokoh agama setempat. Prosedur pengumpulan data primer dihimpun lewat teknik observasi langsung, wawancara mendalam, serta studi epigrafi terhadap tinggalan inskripsi nisan kuno Arab-Persia. Temuan penelitian menunjukkan bahwa kompleks makam tersebut memuat lebih dari 215 nisan, termasuk penanda makam Syekh Mahmud setinggi dua meter yang wafat tahun 44 Hijriah. Kehadiran artefak ini mengukuhkan peran Barus sebagai bandar internasional multi etnis sekaligus gerbang masuknya islamisasi abad ke-7 masehi. Simpulan utama menegaskan bahwa integrasi peninggalan purbakala lokal ke dalam kurikulum terbukti andal mendongkrak ketangkasan spasial siswa secara berkelanjutan. Guru IPS direkomendasikan merancang draf modul ajar berbasis pemanfaatan peninggalan arkeologis secara konsisten.